Adaptive Fuzzy Finite-Time Bipartite Containment Control for Stochastic Multi-Agent Systems - Wu, Ying; Xue, Hong; Tian, Ying; Liang, Hongjing (International Conference on System Science and Engineering (Online), 2020)
This paper proposes the adaptive fuzzy finite-time bipartite containment control scheme for stochastic multi-agent systems subject to dead zone and sensor faults. The fuzzy logic systems are employed to compensate unknown nonlinear functions. The adaptive compensation control method is used to overcome the obstacle caused by sensor faults. Moreover, unlike most existing finite-time control results, the proposed control method can be applied to stochastic MASs and the nonlinear functions of the systems are completely unknown. In addition, the tracking differentiator is used to avert the problem of "explosion of complexity" existed in backstepping method. Moreover, the closed-loop stability of stochastic multi-agent systems is proved to be the semi-global practical finite-time stability in probability. Finally, simulation results are presented to verify the availability of the proposed control scheme.